Ammonia concentration and bacterial evaluation of feline whole blood and packed red blood cell units stored for transfusion (International Journal of Health, Animal Science and Food Safety, 2014)
Ammonia concentrations increase in human, canine and equine WB and PRBC units during storage. The aim of this study was to determine the effect of storage on ammonia concentration in feline WB and PRBC units stored in a veterinary blood bank and to evaluate possible correlations with bacterial contamination. Ammonia concentration was evaluated in 15 WB units and 2 PRBC units on day 1 and at the end of storage after 35 and 42 days, respectively. In an additional 5 WB units and 4 PRBC units ammonia concentrations were determined daily until the day the normal reference range was exceeded and then weekly to the end of storage. All units were evaluated for bacterial contamination. Ammonia increased markedly during storage as a linear function over time. On the 35th and 42th day of storage at 4±2°C mean±SD ammonia concentration reached 909±158 µg/dl and 1058±212 µg/dl in WB and PRBC units, respectively. Bacterial culture was negative in all units. High ammonia concentrations in stored WB and PRBC units could result in toxicity, particularly in feline recipients with liver failure, portosystemic shunts or those receiving large transfusion volumes. Clinical in vivo studies evaluating the effects on recipients should be performed.
Keywords: Feline; Transfusion medicine; Whole blood unit; Packed red blood cell unit; Ammonia; Bacterial contamination